A genetic variant in GLP1R is associated with response to DPP-4 inhibitors in patients with type 2 diabetes. Issue 44 (November 2016) - Han, Eugene; Park, Hye Sun; Kwon, Obin; Choe, Eun Yeong; Wang, Hye Jin; Lee, Yong-ho; Lee, Sang-Hak; Kim, Chul Hoon; Kim, Lee-Kyung; Kwak, Soo Heon; Park, Kyong Soo; Kim, Chul Sik; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Incretin hormone-based therapy in type 2 diabetes has been widely used, and dipepdityl peptidase-4 (DPP-4) inhibitors, which prevent incretin degradation, have become popular oral hypoglycemic agents. The efficacy of DPP-4 inhibitors varies from individuals, and factors determining responses to DPP-4 inhibitors have not been fully established. We aimed to investigate whether genetic variations in glucagon-like peptide (GLP-1) receptor are associated with responses to DPP-4 inhibitors in patients with type 2 diabetes. Genetic variations of rs3765467 in GLP-1 receptor were explored in 246 patients with type 2 diabetes who received DPP-4 inhibitors treatment for 24 weeks in addition to previous medication. Patients with glycated hemoglobin (HbA1c) > 7% and who were naive to any DPP-4 inhibitors were enrolled. Responders were defined as those who showed a > 10% reduction in HbA1c after DPP-4 inhibitor treatment. DPP-4 inhibitors improved glycemic parameters and lipid profiles. Compared to the major genotype (GG), a larger proportion of patients with the minor allele genotype (GA/AA) were responders ( P = 0.018), and also showing greater HbA1c reductions (1.3 ± 1.1 vs 0.9 ± 1.2%; P = 0.022). This genetic effect remained significant even after adjustment for other confounding factors (OR = 2.00, 95% CI = 1.03–3.89). Polymorphism in the GLP-1 receptor may influence DPP-4 inhibitor response. Further studies in larger population will help determine the association between genetic variation and interindividual differences in DPP-4 inhibitor therapy.